Human Rights-Based Learning Design in Higher Education - Mariyani, Mariyani; Nastiti, Dian (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2022)
The purpose of this study is to provide an overview of learning designs that can support human rights-based education in higher education. This is because it is still found during the learning process in the classroom that students’ opportunities are still minimal because they are centered on the lecturer. So we need an innovative and participatory learning model that is centered on students. The method is a literature review. Literature studies can be obtained from various sources, both journals, books, documentation, internet and libraries. The literature study method is a series of activities related to the methods of collecting library data, reading and taking notes, and managing writing materials. The data analysis used is descriptive. The results of this study that 1). The Student Centered Learning approach in Higher Education is one of the ways to realize human rights-based education; 2). Classes as laboratories must design adult learning (Andragogy) which is characterized by freedom of opinion and independent initiative and 3). Innovative learning based on human rights can use learning methods of brainstorming, case studies and value clarification. These three learning designs provide space for students to actively participate. With this learning design, it is hoped that it will train students to uphold human rights, especially during the learning process